Enhancing Reading Comprehension Through Extensive Reading - Fergina, Ana; Ghazy, Ahmad; Prancisca, Stella; Aminah, Syarifah; Ananda, Elsa (FKIP - Universitas Tanjungpura, 2024)
Numerous studies support extensive reading as beneficial for second language learners, enhancing vocabulary, grammar, writing, and overall English proficiency. However, there is still a small number of research on how this technique influences students' ability to answer reading comprehension questions. Extensive reading and reading comprehension have quite different reading goals. Extensive reading aims to make readers enjoy reading material and can choose reading materials according to the reader's level. Meanwhile, reading comprehension emphasizes students' level of understanding about the details of reading material. This research aims to look at the effect of extensive reading strategies on students' ability to answer reading comprehension questions. The method used in this research is experimental by using